Proceedings of the 2003 Conference on Universal Usability 2002
DOI: 10.1145/957205.957209
|View full text |Cite
|
Sign up to set email alerts
|

Design studies for a financial management system for micro-credit groups in rural india

Abstract: In this paper we describe the design process, results and observations obtained in designing a user interface for managing community-based financial institutions in rural India. The primary users are semi-literate village women from local communities. We present detailed observations from our field visits and the resulting evolution in our design vision. We describe a successful design artifact that is the result of this process, and list several important features that contributed to its success. We conclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Research studies have demonstrated that pictorial interfaces, fully embedded into cultural contexts, local meanings (Lalji & Good, 2008;Medhi et al, 2006) and user preferences (Frommberger & Waidyanatha, 2017;Lalji & Good, 2008), with little or no text are more useful for low-literate users than text-heavy apps (Medhi, Prasad, & Toyama, 2007;Medhi et al, 2006;Parikh, Ghosh, & Chavan, 2003). However, a few studies suggested augmenting, rather than eliminating, textbased features, as text could be perceived a status symbollack of it would encourage stigmatization of low-literate.…”
Section: User Interface Design For Low-literate Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies have demonstrated that pictorial interfaces, fully embedded into cultural contexts, local meanings (Lalji & Good, 2008;Medhi et al, 2006) and user preferences (Frommberger & Waidyanatha, 2017;Lalji & Good, 2008), with little or no text are more useful for low-literate users than text-heavy apps (Medhi, Prasad, & Toyama, 2007;Medhi et al, 2006;Parikh, Ghosh, & Chavan, 2003). However, a few studies suggested augmenting, rather than eliminating, textbased features, as text could be perceived a status symbollack of it would encourage stigmatization of low-literate.…”
Section: User Interface Design For Low-literate Usersmentioning
confidence: 99%
“…For low-literate users picture-based interfaces are often the most effective way of interaction with mobile computing technology (e.g. (Frommberger & Waidyanatha, 2017;Medhi et al, 2007;Parikh et al, 2003) and further in Section 2.2).…”
Section: Picture-based Interface Designmentioning
confidence: 99%
“…Studies on the use of a GUI by rural communities with strong oral traditions suggest that members can more easily identify cultural icons and visualizations than using text-based technologies [15,16]. Visualizations of culture have a history from the earliest humans (e.g.…”
Section: Can Visualization Bridge the Gaps?mentioning
confidence: 99%
“…More specifically, it appears that static hand-drawn representations are better understood than photographs or icons . Some authors note that the use of numbers is acceptable, as many non-literate people can read numerical digits (Parikh et. al., 2003a;Parikh et.…”
Section: Related Workmentioning
confidence: 99%
“…Some authors note that the use of numbers is acceptable, as many non-literate people can read numerical digits (Parikh et. al., 2003a;Parikh et. al., 2003b).…”
Section: Related Workmentioning
confidence: 99%